2012
DOI: 10.1186/1756-0500-5-493
|View full text |Cite
|
Sign up to set email alerts
|

Robust reference intervals for Liver function test (LFT) analytes in newborns and infants

Abstract: BackgroundReference intervals (RIs) are ranges of upper and lower limits of a given analyte which are used for a laboratory test to determine whether a disease is present or absent or to know if the patient is at risk for future disease states. In Ethiopia, a country with highly diversified population groups and geographical sites, there are no established RIs to metabolic analytes including the liver function test (LFT) analytes for the pediatric population though it has been known that liver function assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
2
13
1
Order By: Relevance
“…Alkaline phosphatase followed a similar trend in being relatively elevated in the first few months of life. The range we report is similar to that of other infants [29,30] and is several-fold higher than that of adult concentrations (32-91 U/L; Beckman Coulter). We noted several episodes of markedly elevated alkaline phosphatase (N 1000 U/L; hyperphosphatasemia), particularly in children 9 mo or older.…”
Section: Discussionsupporting
confidence: 84%
“…Alkaline phosphatase followed a similar trend in being relatively elevated in the first few months of life. The range we report is similar to that of other infants [29,30] and is several-fold higher than that of adult concentrations (32-91 U/L; Beckman Coulter). We noted several episodes of markedly elevated alkaline phosphatase (N 1000 U/L; hyperphosphatasemia), particularly in children 9 mo or older.…”
Section: Discussionsupporting
confidence: 84%
“…When similar studies in the literature are examined, the most important point missed is analyzing the tests one by one in the outliers or RI calculation [17,20]. In the related studies, we think that one of the reasons of the difference especially in the region-based comparisons could be not analyzing the correlations between tests.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, as in other studies in the literature, tests should be evaluated by considering together, not separately [1][2][3][4][5][6][7][8]16,17,20]. In our study, RIs of the individuals aged 18-70 were identified by a new Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 10/8/15 9:48 AM approach.…”
Section: Discussionmentioning
confidence: 98%
“…The inclusion and exclusion criteria and data collection and analysis were described in our recent publication [1]. Cord blood (from newborns) and venous blood samples (from infants) were collected and analyzed using direct ISE analyzer (AVL 9181, Roche diagnostics GmbH, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…This work is an extension of the study that we have recently published [1]. A test for electrolytes mostly includes the measurement of sodium (Na + ), potassium (K + ) and chloride (Cl - ) ions.…”
Section: Introductionmentioning
confidence: 99%